Nonocclusive mesenteric ischemia in patients with methamphetamine use. Issue 6 (June 2018) - Anderson, Jamie E.; Brown, Ian E.; Olson, Kristin A.; Iverson, Katherine; Cocanour, Christine S.; Galante, Joseph M.
Abstract : BACKGROUND: Data suggest that methamphetamine may increase the risk of nonocclusive mesenteric ischemia (NOMI). We describe patterns of presentation and outcomes of patients with methamphetamine use who present with NOMI to a single institution. METHODS: This is an observational study of patients from January 2015 to September 2017 with methamphetamine use who presented with NOMI at an academic medical center in Northern California. We summarize patient comorbidities, clinical presentation, operative findings, pathologic findings, hospital course, and survival. RESULTS: Ten patients with methamphetamine use and severe NOMI were identified. One patient was readmitted with a perforated duodenal ulcer, for a total of 11 encounters. Most presented with acute (n = 3) or acute-on-chronic (n = 4) abdominal pain. Distribution of ischemia ranged from perforated duodenal ulcer (n = 3), ischemia of the distal ileum (n = 1), ischemia of entire small bowel (n = 2), and patchy necrosis of entire small bowel and colon (n = 5). Six patients died, three within 1 week of admission and three between 3 months and 8 months. CONCLUSION: Methamphetamine use may be associated with significant microvascular compromise, increasing the risk of mesenteric ischemia. Providers in areas with high prevalence of methamphetamine use should have a high index of suspicion for intestinal ischemia in this patient population. Patients with methamphetamine use admitted for trauma or other pathology may be at particular risk of ischemia and septic shock, especially in the setting of dehydration. Use of vasoconstrictors in this patient population may also exacerbate intestinal ischemia. LEVEL OF EVIDENCE: Therapeutic Case series study, level V.